Silver nanoparticles enhance Pseudomonas aeruginosa PAO1 biofilm detachment. (June 2014) - Loo, Ching-Yee; Young, Paul M.; Cavaliere, Rosalia; Whitchurch, Cynthia B.; Lee, Wing-Hin; Rohanizadeh, Ramin
Abstract Objectives: Silver nanoparticles (AgNPs) with a size ranging from 7 to 70 nm were synthesized using the ascorbic acid-citrate seed-mediated growth approach at room temperature. Methods: The 8 nm silver particles were prepared using gallic acid in alkaline conditions and used as seed to prepare AgNPs. Results: The presence of ascorbic acid and citrate allows the regulation of size and size distribution of the nanoparticles. The increase in free silver ion-to-seed ratio (Ag+/Ag0) resulted in changes of particle shape from spherical to pseudo-spherical and minor cylindrical shape. Further, a repetitive seeding approach resulted in the formation of pseudo-spherical particles with higher polydispersity index and minor distributions of tetrahedral particles. Citrate-capped AgNPs were stable and did not agglomerate upon centrifugation. The effect of AgNPs on biofilm reduction was evaluated using static culture on 96-well microtiter plates. Results showed that AgNPs with the smallest average diameter were most effective in the reduction of Pseudomonas aeruginosa biofilm colonies, which accounted for 90% of removal. Conclusion: The biofilm removal activities of the nanoparticles were found to be concentration-independent particularly for the concentration within the range of 80–200 µg/mL.